Juvenile tillaux fracture in an adolescent basketball player - Cassas, K.; Jamison, J. P. (The Physician and Sportsmedicine, 2005)
Forced external rotation of the foot may cause a syndesmosis or high ankle sprain in an adult, but in a teenage patient, a juvenile Tillaux fracture may occur if the tibial physis has not yet closed. Diagnosis is made with plain radiographs, but CT may be necessary to determine the true articular displacement. Closed reduction with casting for 6 weeks is usually sufficient for most nondisplaced or minimally displaced fractures. Patients with more than 2 mm of displacement, as in this case of a 16-year-old basketball player, should be referred to an orthopedic surgeon. Complications include residual angular deformity and premature osteoarthritis. Most patients are able to return to full activity at 3 months postinjury.